Experiential structure of extended realities (XR):: Approach to the narrative from the body and its contexts. (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2020)
Immersive experiences have peculiarities at the receptive level that do not occur in any other artistic or communication medium. The sense of presence, the continuous interaction with the space or the first-person experience are some of them. This article intends to shed some light delving into the embodiment nature of the immersive and interactive experience creations to ultimately draw some conclusions that can serve future creators.
Keywords: Narrative; Immersive; iteractive; Experiental; Body